Learning from the llama: on the broad contours of cultural contributions and geographic expansion - Emily Wakild (História, Ciências, Saúde: Manguinhos)
Abstract The llama (Lama glama) is the largest domesticated animal species from South America and is today found worldwide. Andean peoples have used the llama for millennia for meat, wool, packing, spiritual etc. In order to know the history of the llama, we must learn about the peoples that have known the animal and the ways those relationships have changed over time. While also considering closely related species, including alpaca, guanaco, and vicuña, this article posits three eras of llama/human entanglements: the era of domestication in pre-Columbian Andean sites; the era of dispersal and co-mingling, from 1530s to the 1890s; and finally popular fads and global appeal.